Facing the void: The experience of Australian care partners and people living with dementia following diagnosis. (December 2021) - Gresham, Meredith D; Low, Lee‐Fay; Phillipson, Lyn; Jeon, Yun‐Hee; Swaffer, Kate; Brodaty, Henry
Abstract: Background: The COGNISANCE (Co‐designing dementia diagnosis and post diagnostic support) project aims to co‐design and produce resources that will improve communication of dementia diagnoses and support for people living with dementia (PLWD) and care partners following diagnosis. Internationally, dementia guidelines reinforce the need for post‐diagnostic support, however PLWD and care partners are frequently dissatisfied. COGNISANCE is being conducted in five countries; Poland, UK, Netherlands, Canada and Australia. This presentation reports on current Australian experiences of support from the perspectives of PLWD, care partners and health and social care practitioners. Methods: Interviews and focus groups were conducted using online video conferencing with 8 PLWD who had been diagnosed with dementia in the past 24 months and 17 care partners. Nineteen health or social care professionals were interviewed individually or in small groups via videoconferencing. Techniques used included word association exercises and projective interviewing ‐ projecting thoughts and feelings onto photographs of an (hypothetical) older couple receiving a diagnosis; and discussion of barriers and facilitators to post‐diagnostic support. Interviews were transcribed and thematically analysed. Results: Key themes were that PLWD and care partners experienced lack of support and direction following diagnosis. Support information given at the time of diagnosis was usually minimal. PLWD described 'an information vacuum' and care partners felt lost, and at a loss of what to do next, or where to find practical or emotional support. The majority of care partners felt abandoned and wanted follow‐up after the diagnostic interview. Health care professionals were concerned but described difficulty in recommending useful supports because of lack of available/appropriate services, lack of knowledge of supports or therapeutic nihilism. Conclusion: Post‐diagnostic support is inadequate and could be improved by follow‐up, better linking with services, provision of information and development of a support plan.